2021
DOI: 10.1155/2021/6687493
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Chronic Prostatitis/Chronic Pelvic Pain Syndrome Increases Anxiety‐Like Behavior: The Role of Brain Oxidative Stress, Serum Corticosterone, and Hippocampal Parvalbumin‐Positive Interneurons

Abstract: Mechanisms of the brain-related comorbidities in chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) are still largely unknown, although CP/CPPS is one of the major urological problems in middle-aged men, while these neuropsychological incapacities considerably diminish life quality. The objectives of this study were to assess behavioral patterns in rats with CP/CPPS and to determine whether these patterns depend on alterations in the brain oxidative stress, corticosterone, and hippocampal parvalbumin-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 81 publications
0
32
0
2
Order By: Relevance
“…In a recent study, Daverey and Agrawal showed that 10 μM of curcumin and riluzole protected astrocytes derived from the human spinal cord against oxidative stress via Nrf2/HO-1 signaling [227]. Previously, Jiang et al showed that curcumin in different concentrations (5,10,15,20, and 25 mM) for 2 h activated Nrf2 target genes in primary spinal cord astrocytes, attenuated the level of intracellular ROS, and decreased oxidative damage and mitochondrial dysfunction [228]. Additionally, i.v.…”
Section: Caffeic Acid Phenethylmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Daverey and Agrawal showed that 10 μM of curcumin and riluzole protected astrocytes derived from the human spinal cord against oxidative stress via Nrf2/HO-1 signaling [227]. Previously, Jiang et al showed that curcumin in different concentrations (5,10,15,20, and 25 mM) for 2 h activated Nrf2 target genes in primary spinal cord astrocytes, attenuated the level of intracellular ROS, and decreased oxidative damage and mitochondrial dysfunction [228]. Additionally, i.v.…”
Section: Caffeic Acid Phenethylmentioning
confidence: 99%
“…Previous reviews indicated the crucial role of oxidative stress and axonal dysregulations in the pathogenesis of Parkinson's disease [11], epilepsy [12], and some other NDDs [13]. Accordingly, cytokines [14], nitric oxide (NO), antioxidant response element (ARE) [15], and other oxidative stress/inflammatory mediators, as well as extrinsic dysregulated pathways, seem to be potential regulators of such pathological conditions. We have also previously provided the role of apoptosis and autophagy following SCI [3]; however, no focus has been yet done on the pivotal role of oxidative stress after SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Our hypothesis was based on the fact that the hippocampus, together with other circuits of the limbic system, amygdala, prefrontal cortex, and others is on the crossroad of fear, memory, and anxiety pathways and that PV+ interneuron inhibitory projects control anxiety [65,66]. Loss of the hippocampal neurons coupled with anxiety-related behavior has been demonstrated in other studies [30,67]. However, it should still be underlined that hippocampal PV + interneurons [68] are involved in the behavioral patterns, including fear and anxiety [69], although they do not influence the mechanism of sleep fragmentation-evoked anxietylike behavior.…”
mentioning
confidence: 99%
“…Recent studies have fully shown that the mechanism of brain-related comorbidities of CP/CPPS is closely related to the brain. Sutulovic et al [ 56 ] showed that anxiety-like behavior in rats with CP/CPPS increased, and the potential mechanisms of observed behavioral alterations could result from an interplay between increased brain oxidative stress, elevated serum corticosterone level, and loss of hippocampal PV + interneurons. They [ 57 ] also showed that CP/CPPS increases susceptibility to lindane-induced seizures in rats associated with the increased level of IL-1 β and IL-6 in the cortex and thalamus.…”
Section: Discussionmentioning
confidence: 99%